Interactive Effects of Low–Pass Filtering and Masking Noise on Word Recognition - Scott, Teri; Green, Walter B.; Stuart, Andrew (Journal of the American Academy of Audiology, 2001)
A word recognition in noise paradigm was employed to examine temporal resolution in individuals with simulated hearing loss. Word recognition scores were obtained for low-pass filtered speech (i.e., cutoff frequencies of 1000, 1250, and 1500 Hz) presented in continuous and interrupted noise at signal-to-noise ratios (SNRs) of–10, 0, and 10 dB. Performance improved with increasing SNR and low–pass frequency filter settings. Generally, word recognition performance was better in the interrupted noise condition than the continuous noise condition. This effect was greatest in the -10 dB SNR condition. Since the continuous/interrupted performance difference steadily declined as a function of low-pass filter cutoff frequency, these findings suggest that one factor leading to poorer speech recognition in individuals with high–frequency hearing impairment may be their dependence on low-frequency hearing channels that are inherently poorer than high-frequency channels for temporal resolution.Abbreviations: ANOVA = analysis of variance, MS = multiple sclerosis, NU-6 = Northwestern University Auditory Test No. 6, SNR = signal-to-noise ratio
Keywords: Hearing loss; temporal resolution; word recognition